Tolvaptan Add-on Therapy to Overcome Loop Diuretic Resistance in Acute Heart Failure With Renal Dysfunction (DR-AHF): Design and Rationale - Minh, Nhat Giang; Hoang, Hai Nguyen; Maeda, Daichi; Matsue, Yuya (Frontiers in Cardiovascular Medicine, 2022)
Background DR-AHF was designed to demonstrate the effectiveness of early tolvaptan (a vasopressin-2 receptor antagonist) add-on therapy in acute heart failure patients with renal dysfunction and clinical evidence of loop diuretic resistance. Methods and Results This is a single-center, open-label, randomized controlled trial, which will enroll 128 patients hospitalized due to AHF. These patients with wet-warm phenotype whose estimated glomerular filtration rates at admission are above 15 and below 60 mL/min/1.73 m2, and cumulative urine output <300 mL in 2 hours after the first dose of intravenous furosemide will be randomly assigned 1:1 to receive a standard care with uptitrating intravenous furosemide alone or a combination therapy with tolvaptan 15mg once daily for 2 days. The standard furosemide treatment will follow the latest Heart Failure Association’s Position Statements. The primary endpoint is the cumulative urine output at 48 hour. The key secondary endpoints include the improvement of fractional excretion of sodium at 6 hour, the total dose of furosemide, and the incidence of worsening renal function at 48 hour. Conclusions Although combination diuretic treatment has gained more insight recently due to its physiologically synergistic action, its advantages may be outweighted by substantial risk of electrolyte disturbances and more severe WRF, and there is no consensus addresses the time point for early starting add-on therapy and the preferred diuretic combination.